The European Partnership for Alternative Approaches to Animal Testing (EPAA): Promoting Alternative Methods in Europe and Beyond - Cozigou, Gwenole (J Am Assoc Lab Anim Sci, 2015)
Here in we introduce the European Partnership for Alternative Approaches to Animal Testing (EPAA) and its activities, which are focused on international cooperation toward alternative methods. The EPAA is one of the leading organizations in Europe for the promotion of alternative approaches to animal testing. Its innovative public–private partnership structure enables a consensus-driven dialogue across 7 industry sectors to facilitate interaction between regulators and regulated stakeholders. Through a brief description of EPAA's activities and organizational structure, we first articulate the value of this collaboration; we then focus on 2 key projects driven by EPAA. The first project aims to address research gaps on stem cells for safety testing, whereas the second project strives for an approach toward demonstration of consistency in vaccine batch release testing. We highlight the growing need for harmonization of international acceptance and implementation of alternative approaches and for increased international collaboration to foster progress on nonanimal alternatives.